Identifikasi Kompetensi Literasi Sains Peserta Didik Pada Pelajaran Ilmu Pengetahuan Alam di SMP Negeri 43 Rejang Lebong - Noni Permatasari (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
The scientific literacy of Indonesian children in recent years has been classified as low and ranked at the bottom among other developing countries. This study aims to determine the scientific literacy competence of students in the interaction of living things and ecosystems subject at Junior High School 43 Rejang Lebong which is a 3T predicate school. The research method is descriptive quantitative, begins with designing test questions based on scientific literacy with 13 students as research subjects, consisting of 7 female and 6 male students. Data analysis was carried out in several stages begin with validation of questions, scoring, and analysis of scientific literacy competency achievements. This study concludes that the scientific literacy ability of students at Junior High School 43 Rejang Lebong is obtained in a low category in 3 aspects of literacy, namely, explaining scientific phenomena, evaluating and designing scientific investigations, and interpreting data and evidence scientifically.